Dietary grape extract can, at an appropriate level, improve the growth performance and antioxidant activity of the white shrimp Litopenaeus vannamei - Chien, Angela; Cheng, Ya Chi; Sheen, Shyn Shin; Kirby, Ralph (Frontiers in Marine Science, 2023)
This study evaluated the growth performance and in vivo antioxidant capacity of the white shrimp, Litopenaeus vannamei, fed diets containing the grape extract Nor-grape 80. A control diet containing 1000 ppm vitamin E without added grape extract and four other diets containing 250, 500, 750 and 1000 ppm grape extract were formulated. Shrimp, twenty 0.02 g of individuals in each aquarium, were randomly assigned to one of the above five treatment diets in triplicate and fed three times daily to satiation for six weeks. The final weight, weight gain percentage and specific growth rate of the shrimp larvae fed diets containing 250 and 500 ppm Nor-grape 80 were significantly higher than those fed the other treatment diets. The levels of superoxide dismutase activity of the shrimp fed diets containing 250 and 500 ppm Nor-grape 80 were significantly higher than those of shrimp fed the control diet. On the other hand, the thiobarbituric acid-reactive substance levels of the shrimp fed diets containing 250 and 500 ppm of Nor-grape 80 were significantly lower than those fed the other diets. Furthermore, the highest levels of dietary Nor-grape 80, namely 750 and 1000 ppm, gave rise to reduced growth performance, as well as lower levels of in vivo antioxidant activity. Therefore, for the best growth performance and highest level of in vivo antioxidant activity, it is suggested that the optimal level of Nor-grape 80 as part of a white shrimp diet falls between 250 and 500 ppm.